Expression of β-Amylase from Alfalfa Taproots - Gana, Joyce A. (American Society of Plant Physiologists, 1998)
Alfalfa (Medicago sativa L.) roots contain large quantities of β-amylase, but little is known about its role in vivo. We studied this by isolating a β-amylase cDNA and by examining signals that affect its expression. The β-amylase cDNA encoded a 55.95-kD polypeptide with a deduced amino acid sequence showing high similarity to other plant β-amylases. Starch concentrations, β-amylase activities, and β-amylase mRNA levels were measured in roots of alfalfa after defoliation, in suspension-cultured cells incubated in sucrose-rich or -deprived media, and in roots of cold-acclimated germ plasms. Starch levels, β-amylase activities, and β-amylase transcripts were reduced significantly in roots of defoliated plants and in sucrose-deprived cell cultures. β-Amylase transcript was high in roots of intact plants but could not be detected 2 to 8 d after defoliation. β-Amylase transcript levels increased in roots between September and October and then declined 10-fold in November and December after shoots were killed by frost. Alfalfa roots contain greater β-amylase transcript levels compared with roots of sweetclover (Melilotus officinalis L.), red clover (Trifolium pratense L.), and birdsfoot trefoil (Lotus corniculatus L.). Southern analysis indicated that β-amylase is present as a multigene family in alfalfa. Our results show no clear association between β-amylase activity or transcript abundance and starch hydrolysis in alfalfa roots. The great abundance of β-amylase and its unexpected patterns of gene expression and protein accumulation support our current belief that this protein serves a storage function in roots of this perennial species.